Welsh Speakers’ Dementia Care - Alzheimer's Society Cymru; Welsh Language Commissioner (Welsh Government, 2018)
The Welsh Language Commissioner and Alzheimer’s Society Cymru have collaborated on a project focussing on the Welsh language and dementia. The research company Wavehill was commissioned to undertake a study of the care and support services delivered to Welsh speakers with dementia. This qualitative research involved consultation with senior officers from local authorities and health boards; academics in the field; care and support providers; and people living with dementia. The purpose of the study was to investigate the main factors and themes influencing the provision, or lack of provision, of Welsh medium dementia health and support services, and learn about the experience of Welsh speakers with dementia of that provision. A round-table event was held with experts in the field to discuss the findings of the research and offer possible policy solutions in response to the difficulties identified. This document summarises the findings of the project. Firstly, it outlines the nature of dementia and highlights the relevant language considerations. It then discusses the policy and legislative developments that are relevant to the field. We then present the findings of our research and the experiences of those living with dementia of the Welsh medium care available to them. Finally, it highlights the difficulties identified and the policy solutions which could, if adopted, make a positive difference to the provision for Welsh speakers.

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les trajectoires d'aînés dans le contexte de l'accès à des services sociaux et de santé en français dans la région d'Ottawa - Kubina, Lucy-Ann; Savard, Jacinthe; Drolet, Marie; Savard, Sébastien; Benoît, Josée (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2018)